Feições tubulares como marcadores de processos de degradação de couraças ferruginosas - Anarda Luísa Sousa Simões (2022)
Duricrusts consist of hardened surfaces with varied compositions cemented by oxides and hydroxides. If the primary metal in the oxide structure is iron or aluminum, duricrust is known as ferruginous/iron or aluminum duricrust (Nahon, 1991). They often occur in environments associated with iron ore mining. The iron crust’s genesis and transformation are complex processes and require further studies. There are tubular and geometrical features related to biological agents described along soil profiles associated with iron crust transformation, specifically pedotubules and rhiziforms structures. This research aims to study these features and their origin, if they could be related to the superficial transformation process that occurred over iron crusts, therefore, being markers of this process. Consequently, the goal is to perform a complete description of tubular features, their organization, and which minerals are present in their structure. In addition, we intent to understand the genesis’ process and the records of their relation with termites and roots, resulting in the genetical model associated with iron crust transformation. The tubular features samples are part of a preview collection allocated on the Applied Geomorphology and Environmental Management`s Lab on Professor Manoel Teixeira da Costa Research Center (GAGEA/CPMTC), collected in Belo Horizonte and Nova Lima, in Quadrilátero Ferrífero, and Datas, in Serra do Espinhaço. In the end of the present study, is possible to conclude that the mineral assembly is formed by iron oxide, mainly goethite, followed by hematite, and some other oxides, subordinately. Is also possible to describe features of degradation and recrystallization of minerals associated with the presence of roots and complementary structures. The result of this complex process appear as ferruginous structures formed by three different phases: the first one is marked by the fragmentation of pre-existing armor levels and the formation of fragments observed in the framework; the second phase marked by the dissolution of fragments, remobilization and reprecipitation of iron and aluminum with plant molds; and the last one characterized by dissolutions, reprecipitations, fragmentations and postdepositional transformations of the tubular features. The associated techniques are macroscopically description, optical microscope description, X-ray diffractometry, direct and indirect isomorphic substitution analysis and Scanning Electron Microscopy (SEM), associated with Energy Dispersive System (EDS), Backscattered electron (BSE) imaging.